4C-Based Learning Model: What, Why, How - Ratminingsih, Ni Made; Budasi, I Gede; Piscayanti, Kadek Sonia; Adnyayanti, Ni Luh Putu Era; Paragae, IGA Pt Novita Sari (JPI (Jurnal Pendidikan Indonesia), 2021)
This article presents theoretical and empirical reviews on the nature, rationale and the implementation of teaching model developing students’ 4C skills in the classroom. It also shares the research result conducted in Teaching English as a Foreign Language (TEFL) Course of English Education Study Program. This descriptive research was conducted in the form of Research and Development Model by Gall, Gall, and Borg which resulted in the development of 4C-based learning model integrated in task-based learning framework. The expert judgement on the quality of the model proved that the developed model gained the mean score of 4.85 (from 5 Likert Scale) which means that the model was considered very good. The 4C-based learning model is a solutive learning model to be used in the 21st century in delivering TEFL course. Thus, it is expected that the lecturers of TEFL Course implement the model regularly to enable student teachers to obtain the required skills later both in their real teaching practicum and in their future career.